The Role And Importance Of Marketing Strategy In Uzbekistan's Integration Into World Tourism Markets - Xudoyarov Anvar Aidjanovich (Global Scientific Publishing, 2025)
In this article, in order to ensure the effective operation of the tourism industry in the world economy, the fierce competition in the tourism market in Uzbekistan, suggestions have been developed on the active use of the elements of the integrated marketing strategy in the field.
Keywords: marketing strategy; concept; integration